Prenatal diagnosis, management, and outcomes of fetuses with tetralogy of Fallot in China after prenatal counseling: a prospective cohort study - Deng, Deng-pu; Qian, Tao; Liu, Yu-hong; Wu, Zhong-shi; Lu, Ting (Frontiers in Pediatrics, 2023)
Objective: The study aimed to monitor fetuses with tetralogy of Fallot (TOF) following prenatal counseling and its influence for parents’ decision to termination the pregnancy. Methods: Fetuses with isolated TOF diagnosed between January 2019 and December 2021 were prospectively enrolled. Follow-up was up to termination or 6 months after operation. Results: Of the 1026 fetuses diagnosed with cardiac defects, 129 were isolated TOF and completed the follow-up. Fifty-five (42.6%) fetuses were terminated, with larger maternal age (OR: 0.893, 95% CI: 0.806-0.989, P =0.031) as the protective factor. Maternal anxiety score, gestational weeks, and the pulmonary to aortic diameter ratio lost significance in multivariate analysis. Subjectively, worries about the prognosis (41.8%) and the possible suffering of the unborn child (18.2%) was the two most common reasons for termination of pregnancy. Prenatal diagnosis was accurate in 73 of the 74 (98.6%) live births. Of the 64 live births surgically repaired in our center, primary repair was performed for 57 (89.1%) with median age of 104 days, valve-sparing repair was achieved for 49 (76.6%). No perioperative death occurred. Conclusions: Termination for fetuses with TOF remains common in China. Live births with TOF can be safely and effectively managed.